ANTIFUNGAL ACTIVITY OF METHANOL EXTRACT OF BLACK CUMIN SEEDS ON Aspergillus sp. - Lia Utami Rahman (Tanjungpura University, 2018)
Aspergillus sp. is a type of pathogenic fungus and can cause pulmonary aspergillosis. This research aims to determine the concentration of methanol extract from black cumin (Nigella sativa) seeds which effective to inhibit the growth of Aspergillus sp. (RMPRB2). This research used poisoned food method with Completely Randomized Design consisting of six treatments with four replications. The results showed that the methanol extract of Nigella sativa seeds could inhibit the growth of fungal isolates from Aspergillus sp. (RMPRB2). The Methanol extract of Nigella sativa with a concentration of 2% and the positive control gave a strong inhibitory activity to the growth of Aspergillus sp. (RMPRB2) with a percentage of 100%. Concentration of 1% is the most effective result because gave a very strong inhibitory activity to the growth of fungal isolates of Aspergillus sp. (RMPRB2).